Pengaruh Media Cerita Bergambar terhadap Pemahaman Nilai Toleransi antar Siswa Berbeda Agama di Sekolah Dasar - Nala 'Ariikah; Wawan Shokib Rondli; Nur Fajrie (JANACITTA, 2026)
The main objective of this study is to analyze the influence and effectiveness of using illustrated story media in increasing students' understanding of tolerance values. The research methodology used is a quantitative approach with a One-Group Pretest-Posttest design. The research sample consisted of 35 fifth-grade students at SD 1 Bulungcangkring, selected using the Saturation Sampling technique. Data were collected through test instruments (pretest-posttest) and non-test instruments such as interviews, observations, and questionnaires. Data analysis was carried out through normality prerequisite tests followed by hypothesis testing using the Paired Sample T-Test and the N-Gain test. The results showed a significant influence of the use of illustrated story media on the understanding of tolerance values. This is evidenced by a significance value of 0.000 < 0.05 in the t-test, meaning the alternative hypothesis (Ha) is accepted. Furthermore, there was an increase in the students' average score from 68.05 during the pretest to 90.55 during the posttest. The N-Gain test resulted in a score of 0.7320, which falls into the high category, indicating that this media is quite effective. The conclusion of this research is that illustrated story media is effective in improving the understanding of tolerance values, particularly in indicators of inter-religious cooperation and mutual assistance.  Abstrak Tujuan utama dari penelitian ini adalah untuk menganalisis pengaruh serta efektivitas penggunaan media cerita bergambar dalam meningkatkan pemahaman nilai toleransi pada siswa. Metodologi penelitian yang digunakan adalah pendekatan kuantitatif dengan desain One-Group Pretest-Posttest. Sampel penelitian terdiri dari 35 siswa kelas V SD 1 Bulungcangkring yang diambil menggunakan teknik Saturation Sampling. Data dikumpulkan melalui instrumen tes (pretest-posttest) dan instrumen non-tes seperti wawancara, observasi, serta angket. Analisis data dilakukan melalui uji prasyarat normalitas yang dilanjutkan dengan uji hipotesis menggunakan Paired Sample T-Test dan uji N-Gain. Hasil penelitian menunjukkan adanya pengaruh yang signifikan dari penggunaan media cerita bergambar terhadap pemahaman nilai toleransi. Hal ini dibuktikan dengan nilai signifikansi 0,000 < 0,05 pada uji t, sehingga hipotesis alternatif (Ha) diterima. Selain itu, terjadi peningkatan nilai rata-rata siswa dari 68,05 saat pretest menjadi 90,55 saat posttest. Uji N-Gain menghasilkan skor 0,7320 yang masuk dalam kategori tinggi, menunjukkan bahwa media ini cukup efektif. Simpulan dari penelitian ini adalah media cerita bergambar efektif dalam meningkatkan pemahaman nilai toleransi, terutama pada indikator kerja sama antar agama dan sikap saling membantu.